2004
DOI: 10.1055/s-2004-830093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuronavigation and Image-Guided Extensive Resection for Adult Patients with Supratentorial Malignant Astrocytomas: A Single-Institution Retrospective Study

Abstract: Neuronavigation has become an effective therapeutic modality and is used routinely for intra-axial tumor removal. This retrospective study was conducted to evaluate the clinical impact of neuronavigation and image-guided extensive resection for adult patients with supratentorial malignant astrocytomas. Between 1990 and 2002, 76 adult patients with pathologically confirmed malignant astrocytomas underwent craniotomy and removal of the tumors at the Toyama Medical and Pharmaceutical University Hospital. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 16 publications
4
29
0
3
Order By: Relevance
“…5,6 The advent of intraoperative neuronavigation has helped in planning a more precise surgical approach to the targeted lesion and thus the use of a minimally invasive craniotomy. 7 A smaller craniotomy flap allows for a shorter duration of anesthesia and surgery, faster recovery, and less need for postoperative admission to the ICU. 8 As well, an awake craniotomy (AC) can be safely used for many supratentorial tumours, allowing for a potentially faster recovery and discharge from the hospital, as short stay or even as day surgery.…”
Section: Résultats Les Données De 329 Patients (âGe Moyen [Et]mentioning
confidence: 99%
“…5,6 The advent of intraoperative neuronavigation has helped in planning a more precise surgical approach to the targeted lesion and thus the use of a minimally invasive craniotomy. 7 A smaller craniotomy flap allows for a shorter duration of anesthesia and surgery, faster recovery, and less need for postoperative admission to the ICU. 8 As well, an awake craniotomy (AC) can be safely used for many supratentorial tumours, allowing for a potentially faster recovery and discharge from the hospital, as short stay or even as day surgery.…”
Section: Résultats Les Données De 329 Patients (âGe Moyen [Et]mentioning
confidence: 99%
“…As well as using of intraoperative neuroimaging technique facilitates performing of safer and complete resection it also reduces hazard ratios. The using of intraoperative neuromonitoring and neuroimaging tools provides high rates of complete resection with low rates of neurological disorders [6,8,10,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, it has been reported that intraoperative neuronavigation in glioma surgery improves functional outcomes of glioma patients. 24,25 However, there are still problems that remain to be resolved. The biggest of these is that navigation surgery can only minimally deal with 'brain shift'.…”
Section: Application Of the Navigation System To Brain Tumor Surgerymentioning
confidence: 99%